Spiritual Leadership and Teacher Performance in Early Childhood Education: A Case Study of Al-Farizi Playgroup - Lucki Hersya Rachman; Diding Nurdin; Abu Bakar; Asep Dikdik (STAI Hubbulwathan Duri, 2025)
Spiritual leadership is increasingly recognized as essential in early childhood education (ECE) for fostering holistic and meaningful learning environments. However, existing leadership models often lack alignment with the cultural and spiritual values of specific contexts, such as Indonesia. This study addresses the gap by developing a spiritual leadership model grounded in Indonesian local wisdom. A qualitative, single-case study was conducted at KB Al-Farizi, Bandung. Participants included one principal and eight teachers selected through purposive sampling. Data were collected via in-depth interviews, participatory observations, and document analysis. Thematic analysis was conducted using NVivo 12 Plus software. The study developed a “Pancasila-based Spiritual Leadership Model for PAUD,” incorporating core Indonesian values such as cooperation, consensus, and local wisdom. Implementation of this model demonstrated positive impacts on teacher performance, including increased motivation (average job satisfaction score of 4.2 out of 5.0), enhanced innovation in teaching practices, and improved interpersonal relationships within the school community. This research contributes to the theoretical development of context-specific spiritual leadership in ECE by embedding Indonesian cultural principles. Practically, it offers a replicable framework for ECE institutions seeking to enhance teacher performance and school culture through culturally rooted leadership practices.